Adult Education Policy and the European Union: Theoretical and Methodological Perspectives (Research on the Education and Learning of Adults, 2014)
The European Union is now a key player in making lifelong learning and adult education policy: this is the first book to explore a range of theoretical and methodological perspectives researchers can use to investigate its role. Readership: Educational Researchers and their students